The relationship between plaque imaging characterization and treatment modality selection. (October 2011) - Schwarz, F; Treitl, M; Grimm, J; Cyran, C; Nikolaou, K; Reiser, M; Saam, T
It is commonly accepted that knowledge of the degree of luminal stenosis alone is insufficient to predict a plaque''s vulnerability. Recently, several imaging techniques, such as high-resolution black-blood magnetic resonance imaging, positron emission tomography/computed tomography, ultrasound, intravascular ultrasound and computed tomography angiography, have emerged that are able to depict the arterial lumen and the vessel wall. This article will describe the potential of these imaging techniques for the identification of vulnerable plaques and will focus on the current evidence that describe the relationship between plaque imaging characterization and treatment modality selection in the coronary and carotid arteries.